Analisis kedisiplinan belajar ips tema indahnya kebersamaan secara daring selama pandemi covid-19 pada peserta didik kelas iv sekolah dasar - Panggih Rahayu; Sukarno Sukarno; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2022)
The purpose of this research is to describe the discipline of learning social studies with the theme of the beauty of togetherness and the constraints of discipline in learning online during the COVID-19 pandemic for 4 grade students of elementary school. This study uses a descriptive qualitative research approach. The research design used is a type of case study field research. Sources of data in this study were students, parents, and class IV teachers at elementary school. Techniques for data collection in this study used questionnaires, interviews, and documentation studies. The data validity test was used source triangulation and technique triangulation. Data analysis of Miles and Huberman's model. Discipline in social studies with the theme of the beauty of togetherness shows moderate category results with indicators of discipline following online learning, discipline in doing assignments, discipline in studying at home, discipline in managing time at home. Discipline learning constraints, namely the constraints of implementing learning carried out at home instead of school and obstacles to learning online only have limited time. The results of the research can add to their treasures and as a reference for students' online learning discipline during the COVID-19 pandemic.